The best of both worlds: Human impact and plant subsistence at the Middle and Late Neolithic semi-agricultural site of Hekelingen III (2900–2500 BC). (2nd May 2017) - Out, Welmoed A.; Dörfler, Walter
Abstract: Archaeological sites of the Dutch Neolithic Vlaardingen group (ca. 3400–2500 BC) are known from a large variety of environments with both dryland and wetland settings and display a variety of site functions. However, large and interdisciplinary archaeobotanical data sets are still scarce, which restricts the understanding of the subsistence of this cultural group. This paper presents a reconstruction of the vegetation, an analysis of human impact and a reconstruction of plant exploitation at the Vlaardingen site of Hekelingen III (2900–2500 BC). The analysis is based on an unusually large data set of four pollen sequences and more than 100 macroremain samples, supported by wood and charcoal data. The pollen data allows a reconstruction of the vegetation before, during and after the Vlaardingen occupation, and shows that human impact was very modest. The macroremain data indicates that there is evidence of emmer wheat, naked barley and flax. Arable weed analysis provides indications of an import of naked barley during at least one occupation phase, which corresponds with the restricted palynological evidence of human impact. In addition, there is plenty of evidence for the exploitation of wild fruits, such as hazelnuts, acorns, crab apples, and water chestnuts, and possibly root tubers of Ficaria verna . Despite indications of long-lasting occupation and a large variety of activities at Hekelingen III, the evidence of the consumption of agricultural products rather than their production and of the collection of a wide range of fruits fits very well with further indications of hunting, fishing and fowling and the absence of heavy, permanent structures. Moreover, the site can be seen as being part of a settlement system in which also other Vlaardingen sites played a role, such as the nearby site of Hellevoetsluis, where permanent occupation was verified and crops were locally cultivated.